Parent-child conflicts and pubertal development in Croatian adolescents - Keresteš, Gordana (Array, 2008)
Conflicts between children and parents are a salient aspect of interaction in families with adolescents. Although during the last few decades many empirical studies on parent-child conflict have been conducted, their results are inconclusive and still much has to be investigated before we get clearer picture about the nature and developmental meaning of parent-child conflict. The aim of this study was to examine conflicts between Croatian adolescents and their parents, as well as to investigate relationships between conflicts and several indicators of pubertal development. The sample consisted of 219 intact families with early adolescents (10 to 15 years old). Children and parents independently completed questionnaire measure of parent-child conflict. Children's self-reports about pubertal development were also collected. Findings revealed that according to both parents' and children's ratings, conflicts were more frequent in mother-child than in father-child dyad. Parents generally perceived higher level of conflicts than children. In all parent-child dyads and according to all informants, conflicts most often occurred over home chores. Age and pubertal status, but not pubertal timing, were related to frequency of conflicts, with child's gender and source of information about conflict (i.e. informant) acting as moderators in these relationships.